1999
DOI: 10.1063/1.869962
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on the stability of streamwise streaks in plane Poiseuille flow

Abstract: The development and stability of streamwise streaks are studied in an air-flow channel experiment at subcritical Reynolds numbers. The streaks were generated by continuous suction through small slots at the wall. The streak amplitude first grows algebraically, and if the amplitude exceeds a certain threshold secondary instability in the form of travelling waves is observed. These waves give rise to high urms values in the region of large spanwise mean flow gradient. Measurements with two hot-wire probes indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 28 publications
4
41
0
Order By: Relevance
“…[4][5][6][7] These studies confirmed that the instability is of inflectional type and that the dominating instability appears as spanwise ͑sinuous͒ oscillations of the streaks. For zero-pressure-gradient boundary layers, the spatial response of a single low-speed streak submitted to a time-harmonic excitation of sinuous or varicose type has been more recently examined experimentally by Asai et al 8 The growth of the sinuous mode was observed to evolve into a train of quasi-streamwise vortices with vorticity of alternate sign.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…[4][5][6][7] These studies confirmed that the instability is of inflectional type and that the dominating instability appears as spanwise ͑sinuous͒ oscillations of the streaks. For zero-pressure-gradient boundary layers, the spatial response of a single low-speed streak submitted to a time-harmonic excitation of sinuous or varicose type has been more recently examined experimentally by Asai et al 8 The growth of the sinuous mode was observed to evolve into a train of quasi-streamwise vortices with vorticity of alternate sign.…”
Section: Introductionsupporting
confidence: 67%
“…17 and 18, presented at the European Fluid Mechanics Conference 6 ͑EFMC6͒ in June of 2006, reveals that the streak amplitude is not the relevant parameter for the breakdown: Streaks of the same amplitude do not always undergo breakdown. Linear stability analysis predicted threshold streak amplitudes of 35% in the plane channel 6 and 26% in boundary-layer flow, 9 values considered higher than those one would expect from experiments. However, Waleffe 25 showed the subcritical nature of streak instability in channel flows.…”
Section: Introductionmentioning
confidence: 90%
“…In particular, it has been observed that streaks of high amplitude become susceptible to secondary inflectional instability leading to breakdown to turbulence. [23][24][25] The aim of this paper is therefore to investigate for the first time the non-modal stability of particle-laden channel flows for different particle mass fraction and relaxation time. Although modal stability analysis shows a stabilization of the flow in the presence of particles, an effective delay of the turbulent onset in channel flows requires also damping of non-modal growth mechanisms.…”
mentioning
confidence: 99%
“…Brandt et al (2003) found that the instability of optimal streaks is convective and that the streaks behave as amplifiers of external noise. The secondary instabilities and the associated modes can be calculated through linear Floquet analyses of the streak base flow extracted from DNS or experiential results (Elofsson, Kawakami & Alfredsson 1999;Ricco, Luo & Wu 2011).…”
Section: Secondary Instabilities Of Streaksmentioning
confidence: 99%